Factores que afectan el mercado de madera aserrada de pino en México - Fuentes López, Martha Elena; García Salazar, José Alberto; Hernández Martínez, Juvencio (Instituto de Ecología, A.C., 2016)
To evaluate the effect of the production and consumption of pine lumber related to variations in prices, the elasticities for supply and demand were calculated in a 23 year period (1980-2003), and fitted to a system of simultaneous equations for supply, demand, price transmission and identity. The results indicate that pine saw wood production is inelastic (0,0748) to the variations in prices and the factors that affect the supply are the used capacity and the installed capacity in forest industries, the minimum wage and the real interest rate. The demand is also inelastic (-0,1743) to the changes in prices in the short and long term, and the factors that affect the lumber consumption, based upon their elasticities, are the delayed consumption and available real income.